NEURO-LINGUISTIC PROGRAMMING-BASED COUNSELING ASSESSMENT APPLICATION DESIGN - Utomo, Prabowo Budi; Akhsani, Rafika; Muluk, Muchammad Saiful; Moch. Kholil (TEKNOLOGI DITERAPKAN DAN JURNAL SAINS KOMPUTER, 2023)
The non-optimal use of technology in counseling assessment makes the problem identification less accurate. Counseling assessment applications that are able to identify problems precisely are a necessity for counselors / counseling guidance teachers. The use of Google API speech to text allows the development of web applications that produce text outputs from voice input that can facilitate the process of diagnosing modalities and sub modalities of counselees / students. The method used in system development is Prototype which has advantages in faster development time. Combined with the Neuro-Linguistic Programming method, it will increase the accuracy of the diagnosis of modalities and sub modalities of counselees/students. The developed application has been tested functionally with a value of 65.63% which is included in the interpretation of 'Feasible', so it can be stated that the developed counseling assessment application is in accordance with user needs and feasible to use.